2020
DOI: 10.1126/sciadv.aba5573
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy via PD-L1–presenting biomaterials leads to long-term islet graft survival

Abstract: Antibody-mediated immune checkpoint blockade is a transformative immunotherapy for cancer. These same mechanisms can be repurposed for the control of destructive alloreactive immune responses in the transplantation setting. Here, we implement a synthetic biomaterial platform for the local delivery of a chimeric streptavidin/programmed cell death-1 (SA-PD-L1) protein to direct “reprogramming” of local immune responses to transplanted pancreatic islets. Controlled presentation of SA-PD-L1 on the surface of poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 49 publications
(88 reference statements)
1
29
0
Order By: Relevance
“…Allogeneic islets were co-delivered with poly(ethylene glycol) (PEG) microgels decorated with chimeric streptavidin/ programmed cell death-1 (SA-PD-L1) to the epididymal fat pad of mice, along with a 2-week rapamycin course. Most recipients maintained islet function for 100 days, and FoxP3 + CD4 + T cells (Tregs) were expanded at the graft site [7]. Similar results were obtained in identical models by immobilizing streptavidin-Fas ligand (SA-FasL) in microgels [71] and scaffolds [72].…”
Section: Delivery Of Tolerogenic Materialssupporting
confidence: 55%
See 1 more Smart Citation
“…Allogeneic islets were co-delivered with poly(ethylene glycol) (PEG) microgels decorated with chimeric streptavidin/ programmed cell death-1 (SA-PD-L1) to the epididymal fat pad of mice, along with a 2-week rapamycin course. Most recipients maintained islet function for 100 days, and FoxP3 + CD4 + T cells (Tregs) were expanded at the graft site [7]. Similar results were obtained in identical models by immobilizing streptavidin-Fas ligand (SA-FasL) in microgels [71] and scaffolds [72].…”
Section: Delivery Of Tolerogenic Materialssupporting
confidence: 55%
“…The adoptive transfer of tolerogenic cells or stem cells has also induced tolerance and/or localized suppression in preclinical and clinical studies [4][5][6] (Figure 2). Finally, bioengineered approaches comprising biomaterials, cells, or combinations thereof [7][8][9] (Figure 3) may provide clues to unveil the mechanisms behind innovative acceptance-inducing strategies (Table 1, Key Table ). The following sections critically review the impact of different strategies on the recipients' response, while addressing the reported biological mechanisms influencing their efficiency.…”
Section: Strategies To Achieve Allograft Acceptance: Advances From Standard-of-care Approachesmentioning
confidence: 99%
“…In addition, in vivo immune rejection still remains a challenge ( 76 ). Recently, various biomaterials-based approaches for islet transplantation have been explored to enhance islet survival and functions and decrease host immune rejection of allogenic islet transplants ( 77 - 83 ).…”
Section: Pancreas Regenerationmentioning
confidence: 99%
“…Similarly, Coronel et al . ( 79 ) have reported that PD-L1-presenting microgels can improve local retention of PD-L1 over 3 weeks in vivo . Therefore, PD-L1-presenting microgels can achieve local induction of allograft islet acceptance in a murine diabetic model.…”
Section: Pancreas Regenerationmentioning
confidence: 99%
“…Mediated by programed death ligand 1 (PDL-1), these monocytes have the ability to cross present the apoptotic debris to CD8+ T cells and tolerize the CD8+ T cell, suppressing antigen specific responses 25 . Immunomodulation via PDL-1 has been shown to enhance transplanted islet graft survival 50 . Thus, despite the large CD8+ T cell population observed in multiple tissues with rPS treatment (Fig.…”
mentioning
confidence: 99%